PENGARUH KOMPETENSI, KOMITMEN ORGANISASI, PELATIHAN DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - Muhammad Dili; Buyung Sarita; La Ode Bahana Adam (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This research aims to empirically examine and analyze the influence of competence, organizational commitment, training and job satisfaction on employees performance at the Wakatobi Regency Inspectorate. This research is explanatory which intends to explain the position of studied variables and the correlation and effects between each variable. The result of the study shows that: (1) Competence, organizational commitment, training and job satisfaction have positive and significant effects on employees’ performance at the Wakatobi Regency Inspectorate. (2) Competence has positive but insignificant effects on employees’ performance at the Wakatobi Regency Inspectorate. (3) Organizational commitment has positive and significant effects on employees’ performance at the Wakatobi Regency Inspectorate. (4) Training has positive and significant effects on employees’ performance at the Wakatobi Regency Inspectorate. (5) Job satisfaction has positive and significant effects on employees’ performance at the Wakatobi Regency Inspectorate. Keywords: competence, organizational commitment, training, job satisfaction and employees’ performance